THE EFFECT OF DESTINATION IMAGE AND TOURIST SATISFACTION ON INTENTION TO REVISIT IN LEMBEH HILL RESORT - Pantouw, Pamela; Pangemanan, Sifrid S. (Universitas Sam Ratulangi, 2014)
Tourism is a economic phenomenon which entails the movement of people to countries or places outside.One of the most interesting tourism places in Indonesia is North Sulawesi. This research will explain about the factors that will increase the customer intentions to revisit Lembeh Hill Resort which are destination image and tourist satisfaction. Lembeh Hill Resort is one of the beautiful resort Lembeh and also considered to be one of the most visited resort in Lembeh, North Sulawesi. This research purpose to find out how to increase customer intention by giving questionnaire. The analytical method used was multiple linear regression analysis, as sample of the research 100 respondent taken from people or tourist that ever come to North Sulawesi. The result of this research means that both destination image and tourist satisfaction has significant influence the intention to revisit in Lembeh Hill Resort in Bitung City. The head and all staffs in Lembeh Hill Resort must give more attention and be concerned about destination image in order to increase intention motivate tourist to revisit in Lembeh Hill Resort. Keywords: destination image, tourist satisfaction, intention to revisit.